Sejarah Perkembangan dan Cakupan Ilmu Balaghah Al-Qur’an dalam Kitab Durus fi Ilmi Balaghah Karya Syeikh Muayyin Daqiq Al-Amili - Ilma Amalia; R. Edi Komarudin (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Qur'an has become the first target of attention for those who have insight and a thirst for knowledge since the first day the Qur'an was revealed. This is because there are so many treasures of learning that can be drawn from the depth of meaning in every verse of the Qur'an. Balaghah science is one of the sciences that focuses on word order in Arabic, especially in the language of the Qur'an. The purpose of this paper is to introduce in a concise manner the scope of the Al-Qur'an balaghah science which is generally divided into three namely ma'ani science, bayan science, and badi' science. In addition, this paper also aims to reveal the origin and context of the science of balaghah as part of an introduction to understanding the science of balaghah in the Qur'an. This paper was prepared using a qualitative method through a literature study approach.